Friction between Reticence and Narrative in Local and Global Interconnections along the Ethical Canadian Diamond Supply Chain - Linda Armano (Wiley, 2023)
This research analyses, through ethnographic research, the cultural interpretations of the global storytelling of Canadian ethical diamonds given by different subjects, belonging to diverse sociocultural and economic contexts, including staff of mining companies, indigenous communities, jewellers, and consumers. The study took place at the two ends of the diamond supply chain, in the Canadian Northwest Territories, where the mines and mining companies are located, and in two jewellery stores in Milan and Bologna, that sell Canadian diamonds. Introducing the concept of the Process of Argumentative Aphasia I highlight how the discourses of the participants in the research on Canadian ethical diamonds were becoming increasingly metaphorically unpronounceable and, therefore, misaligned with the official storytelling as I approached the mining context; whereas moving towards the sales contexts, the argumentative contents of the jewellers' and consumers' speeches were more aligned with the contents of the global advertising narratives on diamonds mined in Canada.